1990
DOI: 10.1183/09031936.93.03101128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on the lipid composition of lung lining fluid and relationship between immunostimulatory lipids, inflammatory cells and foamy macrophages in extrinsic allergic alveolitis

Abstract: Normal lung lining fluid suppresses lymphoproliferative responses. This effect is mediated by the major phospholipid components, but minor lipid components can stimulate lymphocyte proliferation. The aim of this study was to discover whether the changes in lung lipid composition reported in patients with extrinsic allergic alveolitis (EAA) might influence the levels of lymphocytes which occur in the lungs of these patients. Since cigarette smokers are less susceptible to EAA, we also investigated the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The concentration of neutral lipids also appears to be increased or reduced in smokers, particularly that of cholesterol, which was detected to be decreased in past studies [96,102], conversely to what was observed in a more recent study conducted on the induced sputum supernatant [99].…”
Section: Cigarette Smoke's Effect On Composition and Abundance Of Sur...supporting
confidence: 48%
See 1 more Smart Citation
“…The concentration of neutral lipids also appears to be increased or reduced in smokers, particularly that of cholesterol, which was detected to be decreased in past studies [96,102], conversely to what was observed in a more recent study conducted on the induced sputum supernatant [99].…”
Section: Cigarette Smoke's Effect On Composition and Abundance Of Sur...supporting
confidence: 48%
“…The concentration of other phospholipids is also significantly dysregulated. A decrease in the concentration of phospholipids was demonstrated in smokers' BAL fluid [101] and CS was proven to alter the lipid composition of surfactant [102], inducing a selective increase in the concentrations of phosphatidylethanolamine, sphingomyelin and phosphatidylglycerol, but not of phosphatidylcholine. An increase in phosphatidylethanolamine was observed elsewhere [103].…”
Section: Cigarette Smoke's Effect On Composition and Abundance Of Sur...mentioning
confidence: 96%
“…In addition, the percentage Iymphocytes is decreased. These differences in the BALF profile suggest a modification of the inflammatory reactions in the lungs, due to smoking [27].…”
Section: Discussionmentioning
confidence: 95%
“…A systematic lipidomic analysis of BAL fluid in subjects with COPD that had achieved smoking cessation was compared with BAL from healthy subjects, and observed a decrease in alveolar lipids, which correlated with a reduction in lung function [ 29 ]. Smoking decreases BAL fluid lipids, especially phospholipids and cholesterol, followed by sphingolipids and glycerolipids [ 32 ]. Decreases in total BAL lipid, total PL, PC 30:0, PC 32:0, and total cholesterol, amongst other lipids, strongly correlated with decreased lung function, which was also observed in the second-hand smoke mice model [ 29 ].…”
Section: Is There a Relationship Between Smoking Status And Lung Chol...mentioning
confidence: 99%